The neural basis of improved cognitive performance by threat of shock. Issue 11 (30th June 2016) - Torrisi, Salvatore; Robinson, Oliver; O'Connell, Katherine; Davis, Andrew; Balderston, Nicholas; Ernst, Monique; Grillon, Christian
Abstract : Anxiety can have both detrimental and facilitatory cognitive effects. This study investigates the neural substrates of a replicated facilitatory effect of anxiety on sustained attention and response inhibition. This effect consisted of improved performance on the Sustained Attention to Response Task (a Go–NoGo task consisting of 91% Go and 9% NoGo trials) in threat (unpredictable electrical shock) vs safe (no shock) conditions. This study uses the same experimental design with fMRI and relies on an event-related analysis of BOLD signal changes. Findings reveal that threat-related cognitive facilitation (improved NoGo accuracy) is associated with greater activation of a right-lateralized frontoparietal group of regions previously implicated in sustained attention and response inhibition. Moreover, these same regions show decreased activation in the Go trials preceding NoGo errors. During NoGo trials, striatal activity is also greater in the threat vs safe condition, consistent with the notion of enhanced inhibitory processing under threat. These findings identify potential mechanisms by which threat of unpredictable shock can facilitate distinct cognitive functions. A greater understanding of the complex interaction of the anxious state and cognitive processes may have critical clinical implications.